A Life-Course Analysis of the Criminogenic Effects of Maternal Cigarette Smoking During Pregnancy: A Research Note on the Mediating Impact of Neuropsychological Deficit - McGloin, Jean Marie (Journal of research in crime and delinquency, 2006)
Research from a variety of disciplines indicates that maternal cigarette smoking MCS during pregnancy is associated with an array of problematic outcomes, including various measures of criminal offending. Although some researchers have applied Moffitt's developmental taxonomy as a framework for understanding this relationship, this line of research has treated MCS as a proxy for neuropsychological deficit rather than a precursor to it. In short, no research has yet tested whether neuropsychological deficit in fact mediates the relationship between MCS and life-course-persistent offending. Using longitudinal data on an inner-city African American cohort, this research found no evidence of such a mediating relationship. The empirical and theoretical implications of these findings are discussed in the context of identifying pathways for future research. ABSTRACT FROM AUTHOR